What Can Financial Technology Learn from Syariah Finance on Ecosystem: Collaboration - Suwinto Johan (Graduate Program of Universitas Tarumanagara, 2023)
Shariah financing is financing based on Islamic values. Shariah financing must meet several requirements. The shariah financing process must follow the shariah process from start to finish. Financial technology companies also need an ecosystem to grow. Financial technology companies can emulate shariah financing. This study aims to discuss the shariah financing ecosystem that can be studied by financial technology. This research uses qualitative research methods. This study conducted a literature study on shariah financing and financial technology financing. The research concludes that financial technology financing can work with financial technology companies to develop shariah financing. Shariah financing and financial technology financing require an ecosystem. Cooperation of shariah financing and financial technology is one of the best solutions for the development of both financings.